Characterization of Haemonchus contortus Excretory/Secretory Antigen (ES-15) and Its Modulatory Functions on Goat Immune Cells In Vitro - Muhammad Ehsan; Javaid Ali Gadahi; Muhammad Waqqas Hasan; Muhammad Haseeb; Haider Ali; Ruofeng Yan; Lixin Xu; Xiaokai Song; Xing-Quan Zhu; Xiangrui Li (Pathogens, 2020)
Small size excretory/secretory (ES) antigens of the Haemonchus contortus parasite have intense interest among researchers for understanding the molecular basis of helminths immune regulation in term of control strategies. Immunomodulatory roles of H. contortus ES-15 kDa (HcES-15) on host immune cells during host−parasite interactions are unknown. In this study, the HcES-15 gene was cloned and expression of recombinant protein (rHcES-15) was induced by isopropyl-ß-D-thiogalactopyranoside (IPTG). Binding activity of rHcES-15 to goat peripheral blood mononuclear cells (PBMCs) was confirmed by immunofluorescence assay (IFA) and immunohistochemical analysis showed that H. contortus 15 kDa protein localized in the outer and inner structure of the adult worm, clearly indicated as the parasite’s ES antigen. The immunoregulatory role on cytokines production, cell proliferation, cell migration, nitric oxide (NO) production, apoptosis, and phagocytosis were observed by co-incubation of rHcES-15 with goat PBMCs. The results showed that cytokines IL-4, IL-10, IL-17, the production of nitric oxide (NO), PBMCs apoptosis, and monocytes phagocytosis were all elevated after cells incubated with rHcES-15 at differential protein concentrations. We also found that IFN-γ, TGF-β1, cells proliferation and migration were significantly suppressed with the interaction of rHcES-15 protein. Our findings indicated that low molecular ES antigens of H. contortus possessed discrete immunoregulatory roles, which will help to understand the mechanisms involved in immune evasion by the parasite during host−parasite interactions.